Obstetrical Management of Fetal Ascites-Induced Dystocia in a Murrah Buffalo - Sheetal, Shailendra Kishore; Sengupta, Dipyaman; Azad, Chandra Shekhar; Singhal, Sumit; Kumari, Rakhi (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present paper describes a case of dystocia due to fetal ascites in a Murrah buffalo and its successful obstetrical management. An eight-year-old full-term pregnant Murrah buffalo was presented with active labour and fetal parts protruding through the vulva; the case was managed by decompression and delivery per vaginum.